2001
DOI: 10.1518/001872001775898188
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lateral Acceleration in Curve Driving: Driver Model and Experiments on a Real Vehicle and a Driving Simulator

Abstract: Experimental studies show that automobile drivers adjust their speed in curves so that maximum vehicle lateral accelerations decrease at high speeds. This pattern of lateral accelerations is described by a new driver model, assuming drivers control a variable safety margin of perceived lateral acceleration according to their anticipated steering deviations. Compared with a minimum time-to-lane-crossing (H. Godthelp, 1986) speed modulation strategy, this model, based on nonvisual cues, predicts that extreme val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
5
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 21 publications
4
129
5
1
Order By: Relevance
“…Finally, as Gibson has already pointed out, kinaesthetic cues also strongly influence the perception of speed [1,14,19]. To simulate vestibular stimuli, accelerations to be perceived by the driver can be rendered by real time generation of simulator cockpit motion, following appropriate vehicle dynamics.…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, as Gibson has already pointed out, kinaesthetic cues also strongly influence the perception of speed [1,14,19]. To simulate vestibular stimuli, accelerations to be perceived by the driver can be rendered by real time generation of simulator cockpit motion, following appropriate vehicle dynamics.…”
Section: Trends In Cognitive Sciencesmentioning
confidence: 99%
“…However, earlier studies have shown that the absence of physical motion in a driving simulator modifies the driver's reactions [19]. Moreover, computational models of self-motion perception [57] and studies performed on a moving-base driving simulator indicate that driver's control strategies on curved roads make use not only of visual, but also of extra-visual information, such as vestibular (see Box 3) and proprioceptive cues [14,58]. So, on the basis of models proposed in earlier studies [58,59], it has been suggested that these cues are used by the driver to control steering and regulate speed.…”
Section: Influence Of Extra-visual Cues In Steeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Vestibular inputs have considerable effects on speed adjustments, especially when driving on curves (Reymond et al, 2001). These effects are not considered in the current model.…”
Section: Main Concepts Of the Steering Modelmentioning
confidence: 99%
“…In [4] a study was carried out to predict motor vehicle collisions in young adults, by making use of a PC-based driving simulator. In [5] the patterns followed by drivers in adjusting the speed in curves is studied by carrying various tests in a motion-based driving simulator. In [6], how the simulator test conditions affect the severity of the 2 of 13 simulator sickness symptoms was studied.…”
Section: Introductionmentioning
confidence: 99%